PENGARUH IMPLEMENTASI MANAJEMEN ASET TETAP DAN IMPLEMENTASI PENGENDALIAN INTERNAL TERHADAP KUALITAS PELAPORAN KEUANGAN (Pada Pemkab/Pemkot Di Wilayah Pemerintahan Provinsi Jabar) - Yani Kurniasih (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
This research was conducted with the background of the phenomena that occur under audit results by the audit Board of the Republic of Indonesia that the poor quality of financial reporting, especially in local government both provincial and city/district. This research was conducted based on theories that already exist which later develoved into a research model in which the model in this study was designed to eximine the quality of financial reporting ands its relevance to the implementation of the asset management and implementation of the internal control. This study aims to test and obtain empirical evidense of research in oder to obtain answers to the problems of research on how much influense of Implementation of the Asset Management and Implementation of the Internal control on the quality of financial Reporting. The benefits of research is to provide a scientific contribution to the science of public sector accounting and solve problems for local goverments in the implementations of task related to improving the quality of local government financial reporting. This study used survey method with descriptive verification approach and type of causal research conducted at 28 local government both provincial and city/district.in west java. The unit of observation is the Departement of local Asset and finance management (DPKAD) Respondents in this study is the Head of departement, Secretary of departement, Head of Accounting and Head of Assets, Auditor of Inspektorat and Auditor of BPK RI representatives of western java . The data obtained through the questionnaiers were analyzed using the technique of component-Based Structural Equation Modeling (CBSEM) and processed using program Partial Least Square-Path Modeling (PLS-PM) The result showed that : the Implementation of the asset management have a significant affect on the quality of financial reporting; the implementation of the internal control system have a significant effect on the quality of financial reporting; Keywords : the Implementation of the Asset Management and The Implementation of the Internal Control system.